Co-Creating OERs in Computer Science Education to Foster Intrinsic Motivation - Lezeth van der Walt; Chantelle Bosch (Education Sciences)
In an era of increasing digital transformation in education, fostering students’ intrinsic motivation and self-directed learning (SDL) is essential, particularly in dynamic fields such as Computer Science Education (CSE). This study explores whether the co-creation of Open Educational Resources (OERs) as renewable assessments can enhance intrinsic motivation and support SDL among postgraduate students. Grounded in Self-Determination Theory, social constructivism, and established SDL models, this research adopted a qualitative, phenomenological design. Data were collected through semi-structured interviews with BEd Honours students who completed an OER co-creation project as part of their final assessment. Interpretative Phenomenological Analysis revealed five core themes: ownership and confidence, personal growth and SDL development, collaboration and connection, motivation and engagement, and challenges and problem solving. The findings suggest that, when students are given autonomy, purpose, and the opportunity to contribute meaningfully, they experience deeper engagement, stronger SDL skills, and a greater sense of academic agency. Informal peer interaction and scaffolded support further enhanced their learning. This study contributes to the growing evidence that open pedagogical practices, particularly renewable assessments, can transform academic culture by positioning students as active participants in knowledge creation and by promoting sustainable, student-centred learning.